An overview of the application of Maqasid Al-Shariah into cartilage tissue engineering - Ahmad Radzi, Muhammad Aa'zamuddin; Hashi, Abdurezak Abdulahi; Munirah, Sha'ban (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Tissue engineering, being part of regenerative medicine approaches has been researched and applied to treat the articular cartilage diseases. It offers benefit to humankind by improving healthcare economics, better treatment options and quality of life among the osteoarthritic patients. It is felt that this promising field requires Islamic essences to be addressed to its concepts and practices. The paper begins with the discussion of the potential of cartilage tissue engineering in overcoming the harms that may impact the healthcare stakeholders (patients, providers, medical professionals, researchers and healthcare authorities). This will be followed by deliberations based on the Maqasid al-Shariah (five higher objectives of Islamic Law), namely, safeguarding of faith, soul, wealth, mind, and offspring. The deliberations illustrate a general idea of cartilage tissue engineering concept and practices in relation to what Islam champions. Islamic Law is comprehensive and incorporates the moral propositions to the medical discipline. It is presented that every legal ruling in Islam has a function to achieve the benefit to human beings or to protect against harm. The application of Maqasid al-Shariah can serve as a practical framework in healthcare setting especially cartilage tissue engineering. It is hoped that this paper will open further discourses to facilitate for a decree by the relevant authority pertaining to the experimentation and practice of tissue engineering, particularly cartilage tissue engineering.